2002
DOI: 10.1007/s00423-002-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative results of surgery for rectal carcinoma as a function of the distance of the tumor from the anal verge: results of a multicenter prospective evaluation

Abstract: Early results are greatly affected by the location of the rectal carcinoma. This applies to both abdominoperineal resection rates and specific postoperative complications, such as anastomotic leak rate and operation morbidity in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
4
16
0
1
Order By: Relevance
“…On the basis of our own results and the data in the literature, laparoscopic procedures can be recommended as highly standardised and safe options for treating colorectal disease [1][2][3][4][5]. A reservation, however, must be noted with regard to the treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 97%
“…On the basis of our own results and the data in the literature, laparoscopic procedures can be recommended as highly standardised and safe options for treating colorectal disease [1][2][3][4][5]. A reservation, however, must be noted with regard to the treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Auf die statistische Auswertung wichtiger Einzelaspekte und Outcome-Kriterien wurde verzichtet [17,18,19].…”
unclassified
“…In rectal cancer patients that underwent sphincter-preserving surgery, some investigators have studied the influence of a diverting stoma for reducing the rate of anastomotic leakage and the serious consequences of sepsis associated with anastomotic leakage (Table 3). [51][52][53][54][55][56][57][58][59][60] Low-level anastomoses are consistently shown to give rise to higher rates of leakage. 12,15,32,51,52 Despite some reports showing low rates of leakage without a diverting stoma, 53 the most widely held opinion seems to be defunctioning of anastomoses 6 cm and below.…”
Section: Mechanism Of Al On Survivalmentioning
confidence: 98%
“…[51][52][53][54][55][56][57][58][59][60] Low-level anastomoses are consistently shown to give rise to higher rates of leakage. 12,15,32,51,52 Despite some reports showing low rates of leakage without a diverting stoma, 53 the most widely held opinion seems to be defunctioning of anastomoses 6 cm and below. 22 Some investigators 13,23,51,54,55 have found that a diverting stoma both protected against the occurrence as well as the consequences of an anastomotic leakage.…”
Section: Mechanism Of Al On Survivalmentioning
confidence: 98%